Judicial application of nushūz: a comparative study between the Afghan and Malaysian legal systems = التطبيق القضائي للنشوز :دراسة مقارنة بين النظامين الأفغاني والماليزي - Ab Razak, Mohamed Rashid; Rahmani, Shujauddin; Mohd Zin, Najibah (Usuli Faqih Research Centre PLT., 2026)
Marital disobedience (nushuz) remains one of the most contested issues in Islamic jurisprudence and family law, with direct implications for spousal rights and family stability, particularly in contexts oscillating between Sharia principles, customary norms, and modern legal frameworks. Previous scholarship has largely focused either on theoretical jurisprudence or on single-country case studies, leaving a gap in comparative research across Muslim-majority states with divergent legal systems, such as Afghanistan and Malaysia. This study aims to analyze marital disobedience through a comparative examination of Afghan and Malaysian Sharia courts, exploring how Islamic jurisprudence interacts with customary practices and codified laws, and highlighting the gap between legal texts and judicial practice. The research employs a comparative legal-doctrinal method, drawing on classical fiqh sources, statutory laws, international reports, and selected case law from both jurisdictions. The study finds that Afghan adjudication is deeply shaped by tribal customs, which undermine women’s procedural safeguards, while the Malaysian system provides a more structured institutional framework with codified rules and procedural guarantees, though unevenly applied across states. The study contributes to the literature by offering a comparative model that uncovers the interplay of law, Sharia, and social context in addressing nusyuz. It recommends legal and judicial reforms that balance the higher objectives of Sharia with contemporary notions of justice. ________________________________________________ تشكّل قضايا النشوز أحد أبرز التحديات في الفقه الإسلامي والقانون الأسري، لما لها من انعكاسات مباشرة على استقرار الأسرة وحقوق الزوجين، خاصة في المجتمعات التي التي تواجه تداخلا بين النصوص الشرعية والأعراف أو التشريعات الحديثة .معظم الدراسات السابقة اقتصرت إما على الجانب الفقهي النظري أو على تجارب محلية منفردة، مع غياب دراسات مقارنة معمقة بين دول إسلامية ذات أنظمة قانونية متباينة، مثل أفغانستان وماليزيا. تهدف هذه الدراسة إلى تحليل ومعالجة قضايا النشوز من خلال مقارنة القضاء الشرعي في أفغانستان وماليزيا، للكشف عن كيفية تفاعل الفقه الإسلامي مع الأعراف المحلية أو التشريعات الحديثة، واستجلاء الفجوة بين النصوص والتطبيق. اعتمد البحث على منهج مقارن، بالاستناد إلى تحليل النصوص الفقهية والتشريعات الرسمية والتقارير الدولية، مع مراجعة أحكام قضائية مختارة من كلا البلدين. أظهرت الدراسة أن النظام الأفغاني يتأثر بعمق بالأعراف القبلية التي تضعف الضمانات القانونية للمرأة، في حين يقدم النظام الماليزي إطارًا مؤسسيًا أكثر تنظيمًا عبر تقنين النشوز وضمانات إجرائية، لكنه يعاني من تفاوت في التطبيق بين الولايات. تسهم الدراسة في إثراء الأدبيات العلمية عبر تقديم نموذج مقارن يكشف أثر السياق الاجتماعي والقانوني على تطبيق أحكام النشوز، وتوصي بضرورة إصلاح تشريعي وقضائي يوازن بين مقاصد الشريعة ومتطلبات العدالة المعاصرة